On the Relationship Between English as a Foreign Language Learners’ Positive Affectivity, Academic Disengagement, and Communication Apprehension - Ma, Yuxia (Frontiers in Psychology, 2022)
This review tends to investigate the related studies on the relationships among positive affectivity as a type of positive psychology construct and academic disengagement and communication apprehension as two types of negative emotions. The negative correlations among communication apprehension, disengagement, and positive affectivity like enjoyment have been verified in the review of the literature. Moreover, little research has been done on the relationship between academic disengagement and communication apprehension. The studies showed that some factors such as encouraging teaching methodologies, positive classroom context, exciting and challenging classroom tasks can act as mediators in the relationship between positive affectivity and communication apprehension. In the end, the pedagogical implications are explicated to foster the language learning quality and to develop a language educational system. Suggestions for further research are provided to develop the existent literature on the relationship between English as a foreign language (EFL) learners’ academic disengagement, communication apprehension, and their positive affectivity.